2017
DOI: 10.1093/chromsci/bmx090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Constituents in Scrophulariae Radix Processed by Different Methods based on UFLC-MS Combined with Multivariate Statistical Analysis

Abstract: Scrophulariae Radix is one of the most popular traditional Chinese medicines (TCMs). Primary processing of Scrophulariae Radix is an important link which closely related to the quality of products in this TCM. The aim of this study is to explore the influence of different processing methods on chemical constituents in Scrophulariae Radix. The difference of chemical constituents in Scrophulariae Radix processed by different methods was analyzed by using ultra fast liquid chromatography-triple quadrupole-time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The initial processing of TCM is important and closely related to the quality of TCM's products 22 . The initial processing of medicinal materials is from the harvest of medicinal parts to the formation of commercial medicinal materials, such as preliminary treatment and drying 23 .…”
mentioning
confidence: 99%
“…The initial processing of TCM is important and closely related to the quality of TCM's products 22 . The initial processing of medicinal materials is from the harvest of medicinal parts to the formation of commercial medicinal materials, such as preliminary treatment and drying 23 .…”
mentioning
confidence: 99%
“…Kim et al ( , 2012 [3,10] and Shin et al [4] reported that iridoid has been isolated from a wide variety of plants, including SB. Ren et al [2] isolated 162 compounds from SN and, similar to Zhang et al, reported that iridoids, iridoid glycosides [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], phenolic acids, phenolic glycosides [30][31][32][33][34][35][36][37][38], flavonoids [39][40][41][42][43][44][45][46], terpenoids [47][48][49][50], organic acids [51,52], and other compounds [53][54]…”
Section: Phytochemicals In Scrophulariae Radixmentioning
confidence: 99%
“…Iridoids and iridoid glycosides [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] are reported to have various biological activities including anti-inflammatory activity, immunomodulatory activity, anti-diabetic effect, and cardiovascular protection effect. In addition, it is known that flavonoids [39][40][41][42][43][44][45][46] isolated from SN have anti-hypertension effects and terpenoids [47][48][49][50] have anti-oxidative activity. Previous studies exhibited the anti-inflammation activity, anti-platelet aggregation activity, and anti-tumor biological activity of phenylpropanoid glycosides [59][60][61][62][63][64][65].…”
Section: Phytochemicals In Scrophulariae Radixmentioning
confidence: 99%
“…Chemical composition has historically presented a bottleneck in understanding of the elusive component‐effect correlation of TCMs. Many factors may lead to changes in the chemical composition of medicinal materials, including harvest season, 5,6 processing methods, 7 and biological and abiotic factors 8–10 . A systematic study of the chemical composition of LJF and LJC could identify the chemical markers that differentiate LJF and LJC, and could clarify their respective properties.…”
Section: Introductionmentioning
confidence: 99%